THE METHODOLOGY FOR USING RELIABLE AND INFORMATIVE TESTS IN THE SELECTION OF FOOTBALL FOR SPORTS - Khudayberganov Olimjon Komiljonovich (Research Focus International Scientific Journal, 2023)
this article offers and recommendations on the selection and orientation of children in the sport of football.